Assessing the ability of output gap estimates to forecast inflation in emerging countries - Nwabisa Florence Ndzama (Russian Journal of Economics)
We find that, while different models used to estimate the output gap in five major emerging economies show similar trends over time, they lead to different conclusions about how well the output gap can predict inflation. This suggests that the choice of model can significantly impact the conclusions drawn about the relationship between the output gap and inflation. The multivariate Hodrick–Prescott filter and the structural vector autoregressive model produce the smallest forecast errors in most cases among the four output gap models considered. We further find some indications of a better inflation forecasting ability of the output gap in countries with inflation targeting, suggesting that the improved transparency related to inflation targeting might support the inflation forecasting process.